Improving The quality of public transportation system : application of simulation model for passenger movement - Bohari, Zulfadly Azizi; Bachok, Syahriah; Mohamed Osman, Mariana (Elsevier, 2014)
Improvement of the railway system in Kuala Lumpur helped to reduce traffic congestion and increase the accessibility and mobility of users. The improvements considered the crowd movement and user behaviors during planning stages. This paper reports the application of simulation software in managing the passenger movement in public transport interchanges. Using Masjid Jamek Interchange as a case study, video recording and manual passenger counting used as data collection methods. The simulation successful modelled the passenger movement pattern, level of services (LOS) and the walking speed. The model also assessed the factors that affect the movement of passenger such as interior design attributes, information signage visibility and pedestrian behaviours.